Human Umbilical Cord Blood Stem Cells Rescue Ischemic Tissues - Park, Dong-Hyuk; Lee, Jeong-Hyun; Eve, David J.; Borlongan, Cesario V.; Sanberg, Paul R.; Chung, Yong-Gu; Cho, Tai-Hyoung (IntechOpen, 2011)
None